Conceptualizing and Presenting a Paradigm Model of Advertising Strategies for Cosmetics and Health Products in Iran's Online Space - Ayoub Pazhouhan; Latifeh Jaferi (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: In today's era, advertising is the most important aspect of product branding in mass media. The current research was done with the aim of conceptualizing and presenting the model of advertising strategies of cosmetics and health products in the online space of Iran.Methodology:  In terms of practical purpose and with a qualitative approach based on Grounded theory, the research was conducted through semi-structured and indepth interviews with 15 academic experts and marketing and sales managers of Arian Kimia Tech Company, using non-probability and purposeful sampling until reaching the theoretical saturation rule.Findings: The results of coding led to the identification of 380 open codes, 75 subcategories and 26 main categories. Consequences such as increasing sales and income, strengthening customer loyalty, improving brand image, improving innovation and product development, and reducing advertising costs were calculated. It is suggested to pay attention to the paradigm model and its components, especially the causal factors, background and strategies, in order to develop advertising strategies for cosmetics and health products in Iran's online space.Originality/Value:  Few studies have been conducted on the advertising strategies of cosmetics and health products in Iran's online space, especially with a qualitative approach, and there is no practical and systematic model or framework in this field, so this study tries to solve this theoretical and research gap to some extent and provide advertising strategies for the health and cosmetic industries in Iran's online space for the marketing and sales managers of the mentioned industries.